Differences in Offline and Online Learning Methods for Cardiac Pulmonary Resuscitation (CPR) Knowledge and Skills In Final Level Nursing Undergraduate Students - Manggar Purwacaraka (IKIP Mataram, 2023)
The survival rate in cases of cardiac arrest outside the hospital is still low, besides that the public's knowledge about CPR is still limited, and there is a critical time limit for performing CPR. Therefore, the role of lay people, including nursing students, in CPR is important. Improving the knowledge and skills of nursing students in CPR through effective learning methods, one of which is using offline and online methods. This study aims to see differences in learning methods between offline and online methods in increasing the knowledge and skills of Cardiac Pulmonary Resuscitation (CPR) in students of STIKes Hutama Abdi Husada Tulungagung. This research is a quasy experimental research with a posttest only control design approach. The research sample consisted of 56 students who were divided into two groups. The research instrument used questionnaires and observation sheets with statistical tests using Mann Whitney. The results showed that learning methods using both offline and online methods could significantly increase respondents' knowledge about CPR (p=0.002) but did not show a significant difference in respondents' skills in performing CPR (p=0.052). The two learning methods both offline and online have their respective effectiveness, where the online method is more effective in increasing students' knowledge and skills on RJP.